Permanent interstitial 125I seed implantation as a salvage therapy for pediatric recurrent or metastatic soft tissue sarcoma after multidisciplinary treatment. Issue 1 (December 2015) - Yao, Lihong; Wang, Junjie; Jiang, Yuliang; Li, Jinna; Lin, Lei; Ran, Weiqiang; Liu, Chen
Abstract Background The management of pediatric recurrent or metastatic soft tissue sarcoma after multimodal treatment remains challenging. We investigated the feasibility, efficacy, and morbidity of permanent interstitial125 I seed implantation under image guidance as a salvage treatment for pediatric patients with recurrent or metastatic soft tissue sarcoma. Methods This was a retrospective study of 10 patients who underwent percutaneous ultrasound or computed tomography (CT) guided permanent125 I seed implantation. Postoperative dosimetry was performed for all patients. Actuarial D90 was 121–187.1 Gy (median, 170.3 Gy). The number of125 I seeds implanted was 6–158 (median, 34.5), with a median specific activity of 0.7 mCi per seed (range, 0.62–0.8 mCi); total activity was 4.2–113.76 mCi. Follow-up time was 6–107 months (median, 27.5 months); no patients were lost to follow-up. Results The overall response rate (complete response + partial response) was 8/10 (80 %), including two patients with complete response (CR) (20 %) and five patients with partial response (PR) (60 %). Local control rates after 1 and 2 years were 70.1 and 62.3 %, respectively, with a mean local control time of 70.6 months (95 % confidence interval (CI) 45.1–96.0). Survival rates after 1 and 2 years were 68.6 and 57.1 %, respectively, with a mean survival time of 65.3 months (95 % CI 34.1–96.5). Three patients died from distant metastasis; one died from local recurrence 12 months after seed implantation. Three patients suffered a grade I skin reaction and one developed ulceration. No severe adverse neurologic sequelae or blood vessel damage occurred. Conclusions Image guided permanent interstitial125 I seed implantation as a salvage treatment appears to have a satisfactory outcome in children with recurrent or metastatic soft tissue sarcoma.